Retelling the stories of our lives everyday narrative therapy to draw inspiration and transform experience - Denborough, David (W.W. Norton & Company, 2014)
Powerful ideas from narrative therapy can teach us how to create new life stories and promote change. Our lives and their pathways are not fixed in stone; instead they are shaped by story. The ways in which we understand and share the stories of our lives therefore make all the difference. If we tell stories that emphasize only desolation, then we become weaker. If we tell our stories in ways that make us stronger, we can soothe our losses and ease our sorrows. Learning how to re-envision the stories we tell about ourselves can make an enormous difference in the ways we live our lives. Drawing on wisdoms from the field of narrative therapy, this book is designed to help people rewrite and retell the stories of their lives. The book invites readers to take a new look at their own stories and to find significance in events often neglected, to find sparkling actions that are often discounted, and to find solutions to problems and predicaments in unexpected places. Readers are introduced to key ideas of narrative practice like the externalizing problems - 'the person is not the problem, the problem is the problem' -and the concept of "re-membering" one's life. Easy-to-understand examples and exercises demonstrate how these ideas have helped many people overcome intense hardship and will help readers make these techniques their own. The book also outlines practical strategies for reclaiming and celebrating one's experience in the face of specific challenges such as trauma, abuse, personal failure, grief, and aging. Quelle/Source: Verlag/Publisher.